The Effect of Cyber bullying Victimization on Counterproductive Work Behavior - Alwansyah, Adam Ahmad; Santi, Evi; Rahmat Syah, Tantri Yanuar (International Journal of Global Operations Research, 2020)
Counterproductive Work Behavior (CWB) is a behvaior that is contrary with the norms and the rules of an organization. CWB can give the big problems in financial and non-financial aspect for an organization or a member of organization . In this study we will show the effect of cyberbullying victimization on CWB in organization. In this research CWB will be analyzed with the level of cyberbullying victimization that is a variabel which is rarely been studied. The object of this research is pest contrl sector that is never studied in previoud research. A questionnaire has been designed and distributed to 585 pest control employees at Indonesia and the data will be analyzed with SEM ( Structral Equation modelling). This research show that cyberbullying victimization give the positive and significant effect to CWB. This illustrates that the higher level of cyberbullying victimization within an organization, the higher CWB rate and otherwise.Counterproductive Work Behavior (CWB) is a behavior that is contrary with the norms and the rules of an organization. CWB can give the big problems in financial and non-financial aspect for an organization or a member of organization . In this study we will show the effect of cyber bullying victimization on CWB in organization. In this research CWB will be analyzed with the level of cyber bullying victimization that is a variable which is rarely been studied. The object of this research is pest control sector that is never studied in previous research. A questionnaire has been designed and distributed to 585 pest control employees at Indonesia and the data will be analyzed with SEM ( Structural Equation modelling). These researches show that cyber bullying victimization give the positive and significant effect to CWB. This illustrates that the higher level of cyber bullying victimization within an organization, the higher CWB rate and otherwise.